A global catalog of primary reptile type specimens - Uetz, Peter; Cherikh, Sami; Shea, Glenn; Ineich, Ivan; Campbell, Patrick D.; Doronin, Igor V.; Rosado, José; Wynn, Addison; Tighe, Kenneth A.; Mcdiarmid, Roy; Lee, Justin L.; Köhler, Gunther; et al. (Zootaxa, 2019)
We present information on primary type specimens for 13,282 species and subspecies of reptiles compiled in the Reptile Database, that is, holotypes, neotypes, lectotypes, and syntypes. These represent 99.4% of all 13,361 currently recognized taxa (11,050 species and 2311 subspecies). Type specimens of 653 taxa (4.9%) are either lost or not located, were never designated, or we did not find any information about them. 51 species are based on iconotypes. To map all types to physical collections we have consolidated all synonymous and ambiguous collection acronyms into an unambiguous list of 364 collections holding these primary types. The 10 largest collections possess more than 50% of all (primary) reptile types, the 36 largest collections possess more than 10,000 types and the largest 73 collections possess over 90% of all types. Of the 364 collections, 107 hold type specimens of only 1 species or subspecies. Dozens of types are still in private collections. In order to increase their utility, we recommend that the description of type specimens be supplemented with data from high-resolution images and CT-scans, and clear links to tissue samples and DNA sequence data (when available). We request members of the herpetological community provide us with any missing type information to complete the list.